2011
DOI: 10.1007/s13205-011-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of hexavalent chromium by Ochrobactrum intermedium BCR400 isolated from a chromium-contaminated soil

Abstract: Hexavalent chromium-resistant Ochrobactrum intermedium BCR400 was isolated from chromium contaminated soil collected from Vadodara, Gujarat. It reduced 100 mg Cr(VI)/L completely in 52 h with initial Cr(VI) reduction rate of 1.98 mg/L/h. The Cr(VI) reduction rate decreased with increase in Cr(VI) concentration from 100 to 500 mg/L. The addition of anthraquinone-2-sulphonic acid (AQS) to culture O. intermedium BCR400 significantly enhanced its chromium reduction rate. The activation energy of AQS-mediated Cr(VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…50 and 10 % of activity was detected at pH 9.0 and 10.0, respectively. Similar observations of the influence of pH on bacterial Cr(VI) reduction have been made by others (Mclean and Beveridge, 2001;Sultan and Hasnain 2007;Desai et al 2008a, b;Kavita and Keharia, 2012). Although Amphibacillus sp.…”
Section: Effect Of Ph and Temperature On Chromate Reductase Activitysupporting
confidence: 83%
See 2 more Smart Citations
“…50 and 10 % of activity was detected at pH 9.0 and 10.0, respectively. Similar observations of the influence of pH on bacterial Cr(VI) reduction have been made by others (Mclean and Beveridge, 2001;Sultan and Hasnain 2007;Desai et al 2008a, b;Kavita and Keharia, 2012). Although Amphibacillus sp.…”
Section: Effect Of Ph and Temperature On Chromate Reductase Activitysupporting
confidence: 83%
“…4). It has been reported the optimal temperature of Cr(VI) reduction to be in the range of 30-40°C (Megharaj et al 2003;Desai et al 2008a, b;Park et al 2000;Pal et al 2005;Kavita andKeharia, 2012 Xu et al 2012). However, chromate reductases from thermophilic Thermus scotoductus SA-01 (Opperman et al 2008) and Bacillus firmus KUCr1 (Sau et al 2010) have been recently identified with an optimum temperature of Cr(VI)-reduction at 65 and 70°C, respectively.…”
Section: Effect Of Ph and Temperature On Chromate Reductase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy for chromium removal offers a high promise as a bioremediation strategy (Garg, Tripathi, and Srinath 2012). Kavita and Keharia (2012) also reported Cr(VI) reduction by Ochrobacterium intermedium BCR400 isolated from chromium-contaminated sites. They observed that a redox mediator known as anthraquinone-2-sulfonate (AQS) enhanced the reduction process of Cr(VI) many fold.…”
Section: Survival Of Bacterial Strains On Cr(vi)mentioning
confidence: 93%
“…Strains of O. intermedium are associated with both human beings and the environment. Some strains are pathogens which cause infection (Möller et al, 1999;Apisarnthanarak et al, 2005); some live in environments polluted by chromium (Kavita and Keharia, 2012), lead (Waranusantigul et al, 2011), and tobacco waste (Yuan et al, 2007), etc.…”
Section: Introductionmentioning
confidence: 99%